Candida albicans Biofilm Heterogeneity and Tolerance of Clinical Isolates: Implications for Secondary Endodontic Infections - Om Alkhir Alshanta; Suror Shaban; Christopher J Nile; William McLean; Gordon Ramage (MDPI AG, 2019)
Aim: Endodontic infections are caused by the invasion of various microorganisms into the root canal system. Candida albicans is a biofilm forming yeast and the most prevalent eukaryotic microorganism in endodontic infections. In this study we investigated the ability of C. albicans to tolerate treatment with standard endodontic irrigants NaOCl (sodium hypochlorite), ethylenediaminetetraacetic acid (EDTA) and a combination thereof. We hypothesized that biofilm formed from a panel of clinical isolates differentially tolerate disinfectant regimens, and this may have implications for secondary endodontic infections. Methodology: Mature C. albicans biofilms were formed from 30 laboratory and oral clinical isolates and treated with either 3% NaOCl, 17% EDTA or a sequential treatment of 3% NaOCl followed by 17% EDTA for 5 min. Biofilms were then washed, media replenished and cells reincubated for an additional 24, 48 and 72 h at 37 °C. Regrowth was quantified using metabolic reduction, electrical impedance, biofilm biomass and microscopy at 0, 24, 48 and 72 h. Results: Microscopic analysis and viability readings revealed a significant initial killing effect by NaOCl, followed by a time dependent significant regrowth of C. albicans, but with inter-strain variability. In contrast to NaOCl, there was a continuous reduction in viability after EDTA treatment. Moreover, EDTA significantly inhibited regrowth after NaOCl treatment, though viable cells were still observed. Conclusions: Our results indicate that different C. albicans biofilm phenotypes grown in a non-complex surface topography have the potential to differentially tolerate standard endodontic irrigation protocols. This is the first study to report a strain dependent impact on efficacy of endodontic irrigants. Its suggested that within the complex topography of the root canal, a more difficult antimicrobial challenge, that existing endodontic irrigant regimens permit cells to regrow and drive secondary infections.